(3GddhaQ CHh XHj(B: s (3QMdI aj CQLGA JMaI eYeGQjIs - Louvre Abu Dhabi (Department of Culture and Tourism, Abu Dhabi, 2017)
The exhibition "Co-Lab: Contemporary art and savoir-faire" was presented within the framework of the Emirati-French Cultural Programme- in dialogue with the Louvre Abu Dhabi. The collaborative project focused on a cooperation between four artists Khalid Shafar, Talin Hazbar, Vikram Divecha and Zeinab Alhashemi, living in the UAE and four historical French manufacturers
English
Keywords: Louvre Abu Dhabi; N400-3990 Art museums, galleries, etc